Relationship between testosterone and cortisol with anthropometric characteristics in professional male soccer players - Lorena Rodríguez García; Halil Ibrahim Ceylan; Ana Filipa Silva; Filipe Manuel Clemente; Beatriz Moreno Vecino; Francisco Tomás González Fernández; Eugenia Murawska-Ciałowicz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Pre-season training has been demonstrated to modify the physical fitness and hormone levels in professional soccer players. The present study aimed to analyze the relationships between testosterone and cortisol with anthropometric characteristics in a professional male soccer team after the pre-season period. Fourteen volunteer professional male soccer players participated in this study. Significant decreases in anthropometric characteristics were found. For biochemical measures, cortisol (13) =-5.25, p=.001, d=-.27), testosterone (t (13) =-8.10, p=.001, d=-.65) and C/T ratio (t (13) =-4.07, p=.001, d =-0.2) significantly increased after the pre-season period. Moreover, moderate negative relationships were observed between the percentage of change in body weight, r=0.61, p=.01, body fat percentage, r=.53, p=.04, and testosterone. The present study revealed that the improvements in body composition after intense training in the pre-season period could stimulate anabolic activities such as increases in muscle mass, which is an important result in terms of quality of performance and prevention of injury risk, especially throughout the competitive soccer season. Testosterone and cortisol should be considered for future research as stress and recovery state indicators. In fact, professional soccer staff can use these parameters in combination with other indicators to optimize workloads and avoid overreaching and overtraining.